(untitled) (Research, Society and Development, 2021)
The aim of this study is to investigate, through an integrative review, the national and international scientific discussion on the implementation of the 2030 Agenda and the Sustainable Cities Program (PCS) in public administration, considering the articles published in the Web of Science database in the period of 2015 to 2020. Thus, 07 studies were selected that could contribute to this research. The year of publication of the study, country of origin of the research, language, published journal and type of document, objective of the study and its contributions were analyzed. The studies analyzed demonstrate the importance of public management in implementing the 2030 Agenda and/or other environmental programs and the absence of mechanisms for evaluating and controlling the performance of goals aimed at sustainable development. Furthermore, multistakeholder partnerships between higher education institutions, private companies, the public sector and civil society are pointed out as fundamental for the implementation of the agenda and/or other programs that deal with socio-environmental management.